Study of activities at Jurong Port main gate (general and bulk cargo) - Cheng, Ting Hui. (2011)
Port gates are intermodal points where goods get into or out of the port to the next destination. Congestion at the port gate is one of the top problems faced by the port. Not only does it reduce the port efficiency, the whole supply chain is affected. This translates into extra cost to the port users. Therefore, there is a need to explore and reduce the congestion problem especially at the outbound gate where more activities are carried out. In this project, Jurong Port outbound gate was chosen. On site observations at the port gate were made to study different classifications of vehicles passing through the gate. Service and arrival rates of the vehicles were calculated to analyse the port gate queuing system. Sharing sessions with the Jurong Port personnel were carried out to find out documentation flow at the gate, types of cargoes carried and their concerns of the port gate. Results showed General Cargo and Batam Trader vehicles spent the longest time at the port gate causing small congestions due to the extra security measures imposed.